Tonal languages speech synthesis using an indirect pitch markers and the quantitative target approximation methods - Thai, Ta Yen; Huy, Hoang Ngo; Tuyet, Dao Van; Ablameyko, Sergey V.; Hung, Nguyen Van; Hoa, Doan Van (Journal of the Belarusian State University. Mathematics and Informatics, 2019)
Synthesizing tones plays an important role in text-to-speech systems of tonal languages. To accomplish this, the two important steps are to determine the pitch markers of voice utterances and synthesize F0 trajectories for lexical tones. In this paper, we propose two efficient algorithms, one of them is to locate the pitch markers at the peaks of the cumulative signal of each voiced part of the input utterance and the other is to generate F0 trajectories of tones with quantitative target approximation (qTA) parameters of Xu model. The experimentation has shown that the proposed algorithms present pitch markers with high accuracy which has enabled us to generate tones with complex shapes.